IUS CONSTITUENDUM TERHADAP NAMA ARTIS YANG DIKOMERSIALKAN DIDALAM BUKU TANPA SEIZIN TOKOH - Lutfiya Arinda Putri Ananta (Magister Hukum Universitas Semarang, 2022)
This study analyzes the void of copyright law of artist names as the main characters of fiction books to explain the protection and limitations on the use of names from related parties losses. Fiction has commercial value and creates legal problems if published without copyright permission of the artist's name. commercialized can affect moral rights, economic rights and normative regulations, especially in literary works. Method in this scientific work is type of normative juridical legal research, with analysis in regulations of the Ius Constituendum of Republic of Indonesia Number 28 of 2014 concerning Copyrights relating the use of famous artists who have been copyright in fanfiction novels. The novelty are based on the use of the artist's name, which can disseminated to the maximum of technology and information media and has a non commercial nature, some parties it has been realized into a book without permission. The results, although the copyright law has not regulated more definitively regarding this matter, preventive protection can still be carried out in the form of a license agreement and the application of a lawsuit or compensation so that the owner of the name still gets his rights.